A minimally designed PD-L1-targeted nanocomposite for positive feedback-based multimodal cancer therapy. (November 2022) - Mei, Yijun; Tang, Lu; Zhang, Lidong; Hu, Jingyi; Zhang, Ziyao; He, Shun; Zang, Jing; Wang, Wei
Graphical abstract: Herein, aPD-L1-PolyMet/BPN nanocomposite (NC) was minimally fabricated through self-assembling black phosphorus nanosheet (BPN), Polymetformin (PolyMet), and anti-PD-L1 antibody (aPD-L1) in one platform for antitumor therapy. After further irradiated by near-infrared laser, the designed NC could achieve effective tumor eradication and metastasis inhibition through positive feedback-based multimodal therapy with active tumor targetability. Abstract: Combining immune checkpoint blockade therapy (ICBT) with other treatment modalities through nanotechnology offers an opportunity to further boost immunity for effective cancer treatment. Herein three-in-one programmed death-ligand 1 (PD-L1)-targeted nanocomposite (NC) was minimally fabricated through self-assembling photothermal agent black phosphorus nanosheet (BPN), chemotherapeutic agent Polymetformin (PolyMet), and immune checkpoint inhibitor anti-PD-L1 antibody (aPD-L1), avoiding the easy degradability of BPN through bridging the electrostatic interaction between PolyMet and BPN. The prepared aPD-L1-PolyMet/BPN NC could precisely target primary tumor through the interaction between aPD-L1 and PD-L1 based on ICBT, and the targeting efficacy was gradually reinforced due to the PD-L1 upregulation in tumor sites after photothermal therapy (PTT), ensuring positive feedback-mediated multimodal antitumor effect during continuous treatment loops. Moreover, the combinational therapy composed of photothermal immunotherapy (PIT), chemotherapy and ICBT strengthened the antitumor efficacy owing to their synergistic mechanism. Meanwhile, the generated positive feedback property during treatment displayed powerful antitumor effect, which not only inhibited primary and abscopal tumor progression, but also prevented tumor metastasis and promoted long-term tumor immune memory establishment. Therefore, this antitumor NC provided a prospective insight into the field of multimodal cancer therapy through rational and minimal design.